The Use of Quiz-Based Digital Media on Student Motivation and Learning Outcomes - Sri Mulyati; Iskandar Iskandar (Universitas Muhammadiyah Enrekang, 2023)
This study aims to see how the use of Quizizz-based digital learning media affects the level of motivation and student learning outcomes. The type of research used is pseudo-experimental research (quasi), with a paired sample t-test research design. The subjects in this study were Level I Economics Education. The research data collection technique used in this study was a test to measure learning outcomes, as well as an observation instrument to see the level of student learning motivation. The research data analysis technique used the t test. Based on the results showed that the research hypothesis was accepted, this was indicated by the coefficient t count> t table. So that the hypothesis which states that there is an average difference between pretest and posttest learning outcomes, there is an effect of using quizizz-based digital learning media in improving student learning outcomes is accepted. As educators in the millennial era, it is important to use technology in the learning process. Technology-based education that is packaged in an attractive and innovative way will certainly involve more active participation from students, so that they are able to develop their potential according to the demands of education in the digital era. Keywords: Digital Quizizz Media, Learning Motivation, Learning Outcomes Abstrak Penelitian ini bertujuan untuk melihat bagaimana pengaruh penggunaan media pembelajaran digital berbasis Quizizz terhadap tingkat motivasi dan hasil belajar mahasiswa. Jenis penelitian yang digunakan adalah penelitian eksperimen semu (quasi), dengan desain penelitian paired sample t-test. Subjek dalam penelitian ini adalah Mahasiswa Tingkat I Pendidikan Ekonomi. Teknik pengumpulan data penelitian yang digunakan pada penelitian ini berupa tes untuk mengukur hasil belajar, serta instrument observasi untuk melihat tingkat motivasi belajar mahasiswa. Teknik analisis data penelitian menggunakan uji t. Berdasarkan hasil penelitian menunjukkan bahwa Hipotesis penelitian diterima hal ini ditunjukkan dengan koefisien thitung > ttabel. Sehingga hipotesis yang menyatakan bahwa terdapat perbedaan rata-rata antara hasil belajar pretest dengan postest, ada pengaruh penggunaan media pembelajaran digital berbasis quizizz dalam meningkatkan hasil belajar mahasiswa diterima. Sebagai Pendidik di era milenial penting untuk menggunakan teknologi dalam proses pembelajaran. Pendidikan berbasis teknologi yang dikemas secara menarik dan inovatif tentu akan lebih banyak melibatkan partisipasi aktif dari para mahasiswa, sehingga mampu mengembangkan potensi sesuai tuntutan Pendidikan di era digital. Kata Kunci: Media Digital Quizizz, Motivasi Belajar, Hasil Belajar